Meristematic activity of the Endodermis and the Pericycle in the primary thickening in monocotyledons: considerations on the PTM - Menezes, Nanuza L. de; Silva, Delmira C.; Arruda, Rosani C. O.; Melo-de-Pinna, Gladys F.; Cardoso, Vanessa A.; Castro, Neuza M.; Scatena, Vera L. [UNESP]; Scremin-Dias, Edna (Academia Brasileira de Ciências, 2005)
A proposta deste trabalho é mostrar uma nova interpretação do meristema de espessamento primário em monocotiledôneas. Anatomia dos órgãos vegetativos das seguintes espécies foi examinada: Cephalostemon riedelianus (Rapataceae), Cyperus papyrus (Cyperaceae), Lagenocarpus rigidus, L. Junciformis (Cyperaceae), Echinodorus paniculatus (Alismataceae) and Zingiberofficinale (Zingiberaceae). A atividade meristemática da endoderme foi observada nas raizes de todas as espécies, no caule de Cyperus, Cephalostemum e Lagenocarpus rigidus, e no traço foliar de Cyperus e folha de Echinodorus. Considerando a continuidade dos tecidos através da raiz, caule e folha, as autoras concluem que no caule o periciclo permanece ativo durante a vida da planta, como um gerador de tecidos vasculares. O Meristema de Espessamento Primário é o periciclo em fase meristemática, juntamente com a endoderme e suas derivadas (ou apenas o periciclo). Próximo ao ápice caulinar, esses tecidos se assemelham a um único meristema, dando origem ao córtex interno e aos tecidos vasculares.

This paper proposes a new interpretation for primary thickening in monocotyledons. The anatomy of the vegetative organs of the following species was examined: Cephalostemon riedelianus (Rapataceae), Cyperus papyrus (Cyperaceae), Lagenocarpus rigidus, L. junciformis (Cyperaceae), Echinodorus paniculatus (Alismataceae) and Zingiber officinale (Zingiberaceae). The endodermis with meristematic activity was observed in the root of all the species, in the stem of Cyperus, Cephalostemum and Lagenocarpus rigidus, and in the leaf trace of Cyperus and leaf of Echinodorus. Considering the continuity of tissues through the root, stem and leaf, the authors conclude that in the stem the pericycle remains active throughout the life of the plant as the generator of the vascular tissue. The Primary Thickening Meristem is in fact the pericycle plus the endodermis and its derivatives (or only the pericycle). Close to the stem apex, the assemblage of seems to be a unique meristem, giving rise to the inner cortex and vascular tissues.
Keywords: Cephalostemon; Cyperus; Echinodorus; Lagenocarpus; Zingiber; endoderme meristemática; periciclo; espessamento primário; Cephalostemon; Cyperus; Echinodorus; Lagenocarpus; Zingiber; meristematic endodermis; pericycle; primary thickening